2022
DOI: 10.1007/s11071-022-08078-y
|View full text |Cite
|
Sign up to set email alerts
|

Hidden attractors in Chua circuit: mathematical theory meets physical experiments

Abstract: After the discovery in early 1960s by E. Lorenz and Y. Ueda of the first example of a chaotic attractor in numerical simulation of a real physical process, a new scientific direction of analysis of chaotic behavior in dynamical systems arose. Despite the key role of this first discovery, later on a number of works have appeared supposing that chaotic attractors of the considered dynamical models are rather artificial, computer-induced objects, i.e., they are generated not due to the physical nature of the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…According to figure 5, equilibrium points are set in chaotic basins of attractions and we can conclude that this the periodic state is hidden. This phenomenon is already shown in literature [38,39].…”
Section: Coexisting Behaviors 321 Self-excited and Hidden Oscillationssupporting
confidence: 73%
“…According to figure 5, equilibrium points are set in chaotic basins of attractions and we can conclude that this the periodic state is hidden. This phenomenon is already shown in literature [38,39].…”
Section: Coexisting Behaviors 321 Self-excited and Hidden Oscillationssupporting
confidence: 73%
“…Kuznetsov et al reported the chaotic hidden attractor in Chua's circuit [3][4][5]. This research has since led to further efforts to locate hidden attractors in various examples [6][7][8][9][10][11].…”
Section: The Modelmentioning
confidence: 99%
“…For instance, for a Hénon map (17) with "classical" parameter values a = 1.4, b = 0.3, we picked up the following matrix K = [−1.1, 0; −0.9, 0.9] and considered the following initial conditions v 0 = [−0.6, 1.3], from which we were able to stabilize (see Fig. 3) the following period-2 UPO: Difficulties in obtaining a guaranteed result of UPO stabilization may be connected with complex dynamics effects such as multistability and possible existence of hidden attractor [26][27][28][29][30][31]. For example, if we consider (17) with parameter values a = 1.49, b = −0.138 given in [32], then from some initial point on the unstable manifold of the saddle O − a self-excited attractor with respect to O − can be visualized and a self-excited periodic attractor can be visualized from vicinity of O + (see Fig.…”
Section: Deep Reinforcement Learning: Implementation In St-model Of P...mentioning
confidence: 99%